Penyusunan Latar Belakang Penelitian Dianggap Bagian Tersulit dalam Pembelajaran Penulisan Artikel Ilmiah - Wahyudin Darmalaksana (UIN Sunan Gunung Djati Bandung, 2024)
This research aims to discuss the difficulties in preparing research backgrounds when writing scientific articles. This research uses a qualitative approach by applying descriptive methods. The research results showed that respondents experienced difficulty in compiling research background when writing scientific articles. The discussion of this research explains that the preparation of the research background procedurally should not start from the beginning when writing a scientific article but should be prepared last after writing all the preliminary components of the scientific article. This research concludes that difficulties in preparing research backgrounds can be overcome by paying attention to writing procedures in the structure of scientific articles.